Challenge Perfectionism: An Interwoven Autoethnographic Discussion of Motherhood - Sur, Deepy (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
This autoethnography investigates the intersection of motherhood and social work with my experience as a South Asian woman. Rarely do accounts of motherhood from racialized women offer a space to respond to the pressure to be perfect. Motherhood and mothering literature has increasingly incorporated the use of stories, voices, and experiences. Using narrative inquiry, I make sense of my memories with my children, particularly as a social worker in practice. I compare these stories to concepts of perfectionism and motherhood layered with South Asian cultural norms. Using this method enables me to analyze interpersonal tensions and social issues as I explore the complexity of feminist concepts and challenge perfectionism. Mommy, why is it so hard to grow up? Even if I try my best, I’m scared I won’t know enough. My dear daughter, nobody is perfect. Is it okay to fail? Only if you fail perfectly.